2014
DOI: 10.1371/journal.pone.0107914
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β-Dependent Phosphorylation Alters DNA Binding, Transactivity and Half-Life of the Transcription Factor USF2

Abstract: The upstream stimulatory factor 2 (USF2) is a regulator of important cellular processes and is supposed to have also a role during tumor development. However, the knowledge about the mechanisms that control the function of USF2 is limited. The data of the current study show that USF2 function is regulated by phosphorylation and identified GSK3β as an USF2-phosphorylating kinase. The phosphorylation sites within USF2 could be mapped to serine 155 and threonine 230. In silico analyses of the 3-dimensional struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Changes in the phosphorylation status are often accompanied with transcription factor regulation. Indeed, it has been shown that USF2 is a phosphoprotein [28,29] and that a number of tumor entities such as prostate cancer [30,31,32,33], hepatocellular carcinoma [34,35,36,37] and breast cancer [38,39,40] are associated with an aberrant USF2 function (for review see [13]). In addition, these cancers are also associated with high expression and activity levels of cyclin-dependent kinase-5 (CDK5) (for review see [41])).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the phosphorylation status are often accompanied with transcription factor regulation. Indeed, it has been shown that USF2 is a phosphoprotein [28,29] and that a number of tumor entities such as prostate cancer [30,31,32,33], hepatocellular carcinoma [34,35,36,37] and breast cancer [38,39,40] are associated with an aberrant USF2 function (for review see [13]). In addition, these cancers are also associated with high expression and activity levels of cyclin-dependent kinase-5 (CDK5) (for review see [41])).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experiments with GSK3β-deficient cells revealed that USF2 transactivity, DNA binding and target gene expression were reduced upon lack of GSK3β. Further, experiments with USF2 variants mimicking GSK3β phosphorylated USF2 in GSK3β-deficient cells showed that phosphorylation of USF2 by GSK3β did not affect cell proliferation but increased cell migration ( Horbach et al, 2014 ). Together, these studies indicate that GSK3β is an important modulator of USF function; however, the exact function of both, GSK3β and USF2 in cancerogenesis appears to be variable and may depend on the cellular context.…”
Section: Phosphorylation-dependent Regulation Of Usfsmentioning
confidence: 99%
“…The action of E 2 through GPER1 not only may be involved on the USF2 protein synthesis or viability, but also on the USF2 activation through several pathways described for GPER1 [ 25 , 39 41 ]. This aspect is of high relevance considering the important role, beside the cell-specificity, that specific phosphorylation plays on the activation of USF protein that modifies its function from tumor suppressor in prostate cancer to tumor promoter in lung cancer and thyroid cancer as recently Horbach et al reported [ 15 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very little information are regarding USF2, and even less about USF2 variants. Our data of sustained USF2 protein expression during the secretory phase in eutopic endometria of women with endometriosis, an invasive estrogen-dependent disease, and the fact that the USF2 action is cell specific and may change its function from tumor suppressor to tumor promoter with invasive characteristics [ 15 , 42 ], suggest that USF2 may be involved in the pathophysiology of the endometriosis.…”
Section: Discussionmentioning
confidence: 99%